Determinants of Income : Hours, Alcohol and Non-cognitive Skills - (:unkn) unknown (My University, 2021)
The determinants of income has been a key area of research in labor economics, and a large part of this has focused on the relationship between education and wages. This ignores the many other ways that income is influenced. I explore additional avenues by which income is determined. I examine how education affects income by influencing the hours of work rather than wages directly. Next explore the mechanism that determines the relationship between drinking and income. And finally I continue exploring the importance of non-cognitive and other skills, particularly as they relate to job sorting and therefore determine income The first chapter uniquely documents the emerging role of education in the well known decline in U.S. male working hours. An insignificant hours difference between high school and college graduates becomes a highly significant 2 hours/week advantage for college graduates within a generation. This growing college hours premium is confirmed in alternate data over a longer time period. Moreover, the growing premium exists throughout the distribution and is not generated by the tails. The increasing premium persists across a wide variety of robustness checks and presents as a widespread phenomenon. The emerging college hours premium increases the overall college earnings premium despite recent trends in the college wage premium. The second chapter uniquely shows that the returns to drinking in social jobs exceed those in non-social jobs. While workers’ social skills yield higher returns in social jobs, controlling for these skills does not change the returns to drinking. This suggests a return beyond sorting on measured social skills. The higher returns in social jobs remain when including individual fixed effects and in a series of robustness exercises. The findings fit the hypothesis that drinking assists the formation of social capital in social jobs. The social capital associated with drinking represents both general and specific capital with a higher return to each in social jobs. The third chapter examines the relationship between education and the changes to occupational sorting in the US. I show a college degree is associated with sorting into all high skill occupations, but is less associated with sorting into high social skill occupations within one generation. I uniquely show that when considering the importance in skills in job sorting, the relationship between both social and math skills determines sorting for the latter generation.